Dialectics of the Business Judgment Rule and General Principles of Good Administration in Land Acquisition and Permitting for Electricity Sector Infrastructure - Wiraantaka, Jaka Adiprasetya; Qadri, Qadri; Aprisaputra, Ronny; Widiatmoko, Ndaru Seto; Noor, Ganis Vitayanty (SIGn Journal of Social Science, 2025)
This study examines the legal issues arising from the State Administrative Court’s overlapping jurisdiction over actions by Electricity SOE Directors that possess hybrid characteristics as both private and public entities. The core issue lies in the legal uncertainty surrounding the boundaries of the administrative court’s absolute competence in determining the business discretion of Directors in national strategic projects. Such actions are frequently drawn into the realm of administrative disputes through the expansion of the meaning of the State Administrative Decision. This study aims to analyze the legal standing of SOE Directors, dissect the dialectics between the BJR doctrine and the General Principles of Good Administration in land acquisition and permitting, and formulate norm reconstruction through internal procedural standardization. The research method employed is normative legal research, using the statute and conceptual approaches through prescriptive analysis of nine primary legal instruments and twenty-eight secondary legal materials. The results indicate that integrating BJR into the General Principles of Good Administration is imperative to protect managerial discretion from excessive judicial intervention. A crucial finding in this study emphasizes that the identification of the source of power, whether contractual or regulatory, is the key to determining the qualification of a decision as a private legal act to activate the exception in Article 2 point a of Law Number 9 of 2004. The implications of this study recommend standardizing SOE internal procedures in line with Supreme Court Circular Number 2 of 2019. This is essential to ensure that disputes arising from a breach of contract by the authority remain within the exclusive competence of the civil court. This effort is undertaken to achieve legal certainty in accelerating national energy infrastructure.